Studi Klinis Ramuan Jamu Antihipertensi pada Pasien Hipertensi Derajat I - Triyono, Agus; Zulkarnain, Zuraida; Mana, Tofan Aries (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Hypertension is a risk factor for cardiovascular disease. Hypertension is one of the main causes of high mortality and morbidity in Indonesia. Utilization of medicinal herbs is an alternative for the treatment of hypertension. The study aimed to determine efficacy of the herbs combination (jamu) compared to hydrochlorothiazide (HCT) and evaluated the safety for hypertention stage I. This research method using an open-label randomized clinical trials with intervention for 56 days. Measurement of day-56 (D-56) showed that herbs decreased sistolic blood pressure to130.15 +17.59mmHg and diastolic at 83.82+9.53 mmHg. There was a significant decrease p = 0.000 (p 0.05), with p mean systolic blood pressure (p = 0.370) and mean diastolic blood pressure (p = 0.412)at D-56. Liver function parameters (SGOT, SGPT) and renal function (urea, creatinine) is still in normal range at the end of intervention. This study showed that herbs combination was an equally effective compared to HCT and safe for hypertension stage I.